Delayed Cerebral Ischemia After Subarachnoid Hemorrhage: Is There a Relevant Experimental Model? A Systematic Review of Preclinical Literature - Goursaud, Suzanne; Martinez de Lizarrondo, Sara; Grolleau, François; Chagnot, Audrey; Agin, Véronique; Maubert, Eric; Gauberti, Maxime; Vivien, Denis; Ali, Carine; Gakuba, Clément (Frontiers in Cardiovascular Medicine, 2021)
Delayed cerebral ischemia (DCI) is one of the main prognosis factors for disability after aneurysmal subarachnoid hemorrhage (SAH). The lack of a consensual definition for DCI had limited investigation and care in human until 2010, when a multidisciplinary research expert group proposed to define DCI as the occurrence of cerebral infarction (identified on imaging or histology) associated with clinical deterioration. We performed a systematic review to assess whether preclinical models of SAH meet this definition, focusing on the combination of noninvasive imaging and neurological deficits. To this aim, we searched in PUBMED database and included all rodent SAH models that considered cerebral ischemia and/or neurological outcome and/or vasospasm. Seventy-eight publications were included. Eight different methods were performed to induce SAH, with blood injection in the cisterna magna being the most widely used (n = 39, 50%). Vasospasm was the most investigated SAH-related complication (n = 52, 67%) compared to cerebral ischemia (n = 30, 38%), which was never investigated with imaging. Neurological deficits were also explored (n = 19, 24%). This systematic review shows that no preclinical SAH model meets the 2010 clinical definition of DCI, highlighting the inconsistencies between preclinical and clinical standards. In order to enhance research and favor translation to humans, pertinent SAH animal models reproducing DCI are urgently needed.